AGREEMENT OPTIONS FOR VALUE-BASED GROUP DECISION ON BUILDING SYSTEM SELECTION - Christiono Utomo (Institut Teknologi Sepuluh Nopember (ITS), 2010)
This paper presents a conceptual model of agreement options on negotiation support to facilitate the solving of group choice decision making problems in civil engineering. Group decision in construction is very complicated since many parties involved. Where a number of stakeholders are involved in choosing a single alternative from a set of solution alternatives, there are different concern caused by differing preferences, experiences, and background. Such civil engineering solutions as alternatives are referred to as agreement options, this paper describes a process of group decision and negotiation on building system selection for highway guardrail by assuring safety to provide barrier. The decision consists of three alternatives solution, three stakeholders and ten criteria. Determination of the optimal solution is based on a game theory model of n-person general sum game with complete information that involves forming coalitions among stakeholders.